EFEKTIVITAS EKSTRAK Hyptis suaveolens (L.) Poit. DALAM MENGHAMBAT PERTUMBUHAN JAMUR Sclerotium rolfsii SECARA IN VITRO - Sherly Aulia Primayani (Serambi Biologi, 2018)
Sclerotium rolfsii is a fungus that has a wide range of host and high pathogenicity that can cause stem rot, root rot, and wilt in plants. Diseases caused by S. rolfsii can be overcome by using synthetic or chemical fungicides. The use of synthetic or chemical fungicides on an ongoing basis can have a negative impact on human health. Natural pesticides derived from plant leaf extracts are explored to treat plant diseases. One of them is Hyptis suaveolens (L.) Poit. The compounds contained in this plant are alkaloids, flavonoids, tannins, and suaveolic acid. This study aims to examine the effect of H. suaveolens (L.) Poit. extract and the most effective concentration in inhibiting the growth of S. rolfsii. H. suaveolens (L.) Poit. leaf extract was prepared by maceration method using 96% ethanol. The leaf extract solution was evaporated using a vacuum rotary evaporator. The concentration used is 0% (control), 5%, 10%, 15%, and 20% with 4 repetitions. The data obtained were analyzed using one way ANOVA and Duncan test. The results showed that H. suaveolens (L.) Poit. leaf extract could inhibit the growth of S. rolfsii and the most effective concentration was at concentration 15% with 56% inhibition percentage.